2020
DOI: 10.14814/phy2.14495
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of bradycardia in premature infants: Aerodigestive–cardiac regulatory–rhythm interactions

Abstract: Objective Eating difficulties coupled with cardiorespiratory spells delay acquisition of feeding milestones in convalescing neonates, and the mechanisms are unclear. Aims were to examine and compare the pharyngoesophageal–cardiorespiratory (PECR) response characteristics: (a) in control neonates and those with recurrent bradycardia spells; and (b) during pharyngeal stimulation when bradycardia occurs versus when no bradycardia occurs. Methods Preterm infants ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 37 publications
0
21
0
Order By: Relevance
“…Central swallowing mechanisms are hierarchical, and are adaptational; for example, when these mechanisms are dysfunctional (as in the absence of swallowing, poor propagation, or poor coordination) other cascading reflexes are triggered such as coughing or apnea/bradycardia/desaturation events 26 28 , 33 , 57 . On the other hand, swallowing is also an important restorative mechanism for cardiorespiratory and aerodigestive homeostasis via effective terminal swallowing 28 , 29 , 33 , 38 , 39 . Thus, what construes as a troublesome symptom (problem) is actually a sign of adaptive skill in ensuring aerodigestive clearance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Central swallowing mechanisms are hierarchical, and are adaptational; for example, when these mechanisms are dysfunctional (as in the absence of swallowing, poor propagation, or poor coordination) other cascading reflexes are triggered such as coughing or apnea/bradycardia/desaturation events 26 28 , 33 , 57 . On the other hand, swallowing is also an important restorative mechanism for cardiorespiratory and aerodigestive homeostasis via effective terminal swallowing 28 , 29 , 33 , 38 , 39 . Thus, what construes as a troublesome symptom (problem) is actually a sign of adaptive skill in ensuring aerodigestive clearance.…”
Section: Discussionmentioning
confidence: 99%
“…Pharyngeal, esophageal, and respiratory characteristics were analyzed as previously published 18 , 19 , 24 , 25 , 38 . (B) Pharyngeal infusion (adaptive state): aerodigestive responses to pharyngeal stimulus were analyzed as previously published and included global (peristalsis and symptoms) and regional (pharynx, UES, esophagus, respiratory) characteristics 24 , 25 , 29 , 38 , 39 , 41 , 42 , 47 , 52 . (C) Oral feeding with milk and barium sulfate (adaptive state): Pharyngeal and esophageal characteristics were measured during oral feeding sessions 24 , 25 .…”
Section: Participants Study Design and Methodsmentioning
confidence: 99%
“…The catheter was placed nasally by the study physician using the pull through technique and secured 27 . Concurrent nasal airflow thermistor (Integra Life Sciences) was utilized to detect respiratory changes and deglutition apnea (DA) events, and electrocardiography was utilized to monitor heart rate changes 10–14,26,28 . The OMC was recorded concurrently via a video camera (Handycam DCR‐SX45; Sony) mounted to the infant's crib and connected to the manometry system's video recording unit (Vid 410 Matrox Morphis, Laborie Medical Technologies) 29 .…”
Section: Methodsmentioning
confidence: 99%
“…Automated algorithms were further adapted to detect esophageal and respiratory changes during OMC (Figure 1). Heart rate changes were analyzed utilizing VivoSense Data Analysis Software (v. 3.6; Vivonoetics) 13,28 . Cross‐system coordination between cardio‐respiratory and foregut systems were analyzed by examining ratios between interactive elements.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the well-developed laryngeal reflexes and coordination of pharyngoesophageal-cardiorespiratory (PECR) responses are essential for the development and maintenance of cardiorespiratory rhythms ( Gewolb and Vice, 2006 ; Hasenstab-Kenney et al, 2020 ). As shown in Table 2 , pharyngeal stimulations cause a decrease of heart rate in premature infants with uncoordinated suck-swallow-respiration rhythms due to the immature laryngeal reflexes and PECR responses, which would aggravate the disturbance of cardiac and respiratory rhythms ( Hasenstab et al, 2019 ; Hasenstab-Kenney et al, 2020 ). ( Gewolb et al, 2001 ; Gewolb and Vice, 2006 ) found that the development and establishment of suck-swallow rhythms were associated with their PMA.…”
Section: The Characteristics Of Circadian Rhythms In Preterm Infantsmentioning
confidence: 99%